Analisis Metode SMART Rekrutmen Guru Baru TK/Paud Lestari Di Kabupaten Simalungun - Putri, Nadillah Dwi; Irawan, Eka (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This research is based on the background of the observations and experiences of researchers, that the system of recruitment of new teachers who are currently running in TK / PAUD LESTARI is still not optimal because they are still doing manual and not computerized methods. As a result, it will slow down the work time of the school in making decisions, searching, inputting, updating, the previous recruitment data of the previous period will also be difficult and require a long time, and the security of data recruitment is also not guaranteed. This study uses a quantitative research approach with the subject of new teacher recruitment research for TK / PAUD LESTARI. Research is carried out in the System Development Life Cycle (SDLC) which is a life cycle or methodology in system development. The conclusion of the results of this study is through the cycle of the System Development Life Cycle (SDLC) which is a life cycle or methodology in developing the system to be even better. Based on the conclusions of the results of this study, it was recommended: the aim of the researchers to conduct this research was to design and create a